Biomechanical measurements in microscopically thin stratum comeum using acoustics. - Gardner, T; Briggs, G (2001)
BACKGROUND/AIMS: This study investigated whether a scanning acoustic microscope (SAM) could be developed to measure changes in the mechanical properties of the microscopically thin external layer of skin, the stratum corneum. The adapted microscope was used to determine the effects of various aqueous reagents, as compared with water, on the thickness, density, compression wave velocity and elastic constant, using 10 microm thin sections of human skin. METHODS: Specimens were exposed to aqueous solutions of glycerol, sodium chloride and alpha-hydroxy caprylic acid (HCA) to investigate permeation and to investigate the effect of these solutions on the above physical properties for signal transmission at a centre frequency of approximately 650 MHz in a path parallel to the epidermal layers. RESULTS: The system of measurement was found to give repeatable results and to provide a reliable indicator of the change in mechanical properties of the stratum corneum that arise from imbibition with different substances. Acoustic measurements of untreated specimen thickness and density agreed well with optical measurements and with previously published measurements, respectively. The trend in change of elastic moduli, however, was not in agreement with the results of the large-scale extensibility tests of Takahashi et al. and Hall and Hill, which used thicker specimens that contained additional epidermal or dermal layers. CONCLUSION: Disparate trends in elastic moduli were believed to be due to the strain rate dependence of the tissues and the different rates of loading applied during testing.